PHARMA, PHYSICIAN NEXUS -A PERIL IN THE OFFING - Yousafzai, Abdul Wahab; Fatimah Saeed (Journal of Ayub Medical College Abbottabad, 2023)
Pharmaceutical companies and healthcare professionals have long been a subject of scrutiny, as their collaboration plays a pivotal role in advancing medical research, promoting evidence-based practices, and fostering dialogue among healthcare practitioners. Together, they have pushed the boundaries of scientific innovation, paving the way for groundbreaking medical advancements. However, ethical concerns arise when such collaborations cross the line into lavish sponsorships for physicians, including all-expenses-paid trips to international conferences and seminars. The opaque ties between the pharmaceutical industry and Physicians cast a shadow on the sanctity of impartial medical practice, particularly in a nation like Pakistan where regulatory frameworks are a work in progress. While the undeniable benefits of collaboration between pharmaceutical companies and medical practitioners are evident, it is imperative to address the ethical implications when such partnerships tread perilously close to the line between ethical collaboration and ethically questionable practices.